THE ROLE OF TERRITORIAL CLUSTERS IN REGIONAL ECONOMIC DEVELOPMENT (Multidisciplinary Journal of Science and Technology, 2026)
This article scientifically and theoretically analyzes the role and importance of territorial clusters in regional economic development. The essence of the cluster concept, their formation mechanisms, and their impact on regional competitiveness are examined. The role of clusters in economic diversification is considered using Uzbekistan as an example. Based on the results obtained, recommendations for improving cluster policy have been developed